2015
DOI: 10.7150/ijbs.13240
|View full text |Cite
|
Sign up to set email alerts
|

Sox4 Expression Confers Bladder Cancer Stem Cell Properties and Predicts for Poor Patient Outcome

Abstract: Genetic and epigenetic alterations have been identified as to contribute directly or indirectly to the generation of transitional cell carcinoma of the urinary bladder (TCC-UB). We have previously found that amplification of chromosome 6p22 is significantly associated with the muscle-invasive rather than superficial TCC-UB. Here, we demonstrated that Sox4, one of the candidate oncogenes located within the chromosome 6p22 amplicon, confers bladder cancer stem cell (CSC) properties. Down-regulation of Sox4 led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…= 79, coverage = 7%). SOX4 overexpression has been studied experimentally and has been reported to be an important contributor in bladder cancer tumorigenesis [81,82]. The hypothesis that SOX4 cooperates with ARID1A and TP53 to initiate bladder carcinogenesis is novel and may merit further experimental investigation.…”
Section: Crso Identified a Novel 3-gene Combination In Bladder Cancermentioning
confidence: 99%
“…= 79, coverage = 7%). SOX4 overexpression has been studied experimentally and has been reported to be an important contributor in bladder cancer tumorigenesis [81,82]. The hypothesis that SOX4 cooperates with ARID1A and TP53 to initiate bladder carcinogenesis is novel and may merit further experimental investigation.…”
Section: Crso Identified a Novel 3-gene Combination In Bladder Cancermentioning
confidence: 99%
“…ALDH is a polymorphic enzyme that is responsible for the oxidation of aldehydes to carboxylic acids, which could prevent cells from oxidative insult and facilitate their survival . The expression of ALDH genes, especially ALDH1, has been reported to be associated with UCSCs and a worse prognosis in a large number of previous studies . The functional role of ALDH1 has also been investigated.…”
Section: Aldh1mentioning
confidence: 99%
“…proved that the downregulation of SOX4 led to the inhibition of cell migration, colony formation, the EMT and reduced sphere formation, ALDH high SP, and tumor formation potential. They found that SOX4 regulates a wide range of genes related to the cell cycle, including CCND1, CDK1, FGFR1, FGFR3, MYB and MYC . In research on other tumors, Tiwari et al .…”
Section: Soxmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of its knockdown include reduced sphere formation and enriched cell population with high levels of aldehyde dehydrogenase [ALDH (high)]; inhibition of cell migration, colony formation as well as MET; and decreased tumor formation potential of urothelial cancer cells [22] . The essential role of αv integrins has been shown in migration, EMT and maintenance of ALDH activity, tumor growth and metastasis.…”
Section: Therapeutic Implications and Challengesmentioning
confidence: 99%